Assessment of ITU-R predictions for ku-band rain attenuation in Malaysia - Khairolanuar, Muhamad Haziq; Ismail, Ahmad Fadzil; Badron, Khairayu; Jusoh, Ahmad Zamani; Islam, Md. Rafiqul; Abdullah, Khaizuran (2014)
This paper presents findings on the assessments carried out pertaining to ITU-R’s predicted rain attenuations. The predictions are put against measurements acquired from a campaign in Kuala Lumpur, Malaysia. The investigation tasks involve generation of annual cumulative distributions using assorted ITU-R recommendations as well as from measured data collected for a period of 20 months. Predicted values generated using established ITU-R rain attenuation prediction models are then compared with measurements values, in order to validate the applicability and effectiveness of each model. Based on the evaluation, it can be suggested that the ITU-R P.618-5 recommendation seems to be a befitting prediction model and capable of generating satisfactory prediction for Malaysia.